ANALISIS DAN PERANCANGAN SISTEM PENJADWALAN DAN SISTEM PENGATURAN UNTUK PERTANDINGAN WING CHUN BERBASIS WEB - Joko Susilo, S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2018)
Technological developments in the digital age today, allowing human use technology such as computers and smartphones for use in all aspects of life. The wing chun organization of Indonesia does not have a computerized system to hold a match. This organization still uses manual system, that is by writing and taking notes on physical documents such as paper. Thus, it needs a system that can simplify the implementation of arrangement, scheduling and recording every game. The scheduling system and the arrangement system for wing chun matches are made using the PHP 5 (Hypertext Preprocessor) programming language, using the CodeIgniter framework, the authors use the PHP programming language because of its open source nature, so that any changes or additions will be greatly facilitated, because of the well-organized CodeIgniter framework. In this study, data collection is collected by conducting interviews and direct observation in the field, in order to obtain information that will be used to design the system, so that the system can run in accordance with user needs. The result of this research is a system used for wing chun matches that can be accessed anywhere by people associated with using communication media such as computers, smartphones that have been connected to the internet. The conclusion of this study is that this system can facilitate match organizers, for matches, game scheduling and detailed game recording. Suggestions for this system is to develop this system with Android or IOS based version due to the development of smartphones that can equalize computer performance with high flexibility. Keyword: Information System, web, scheduling, settings, tournament